The Impact of Technology Media Applications on Aspects of Student Responsibility on Physical Education Learning - Dhani Agusni Zakaria; Sumbara Hambali; Silvy Juditya; Henry Asmara; Sutiswo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to find out how much impact the use of technology media in the period of limited face-to-face learning has on aspects of student responsibility in Physical Education learning. The method used is to use an ex-post facto quantitative  approach. The population in this study was all students at SMKN 10 Bandung,  with the samples in this study being class XII Karawitan 1, 2, and 3 students. The sampling technique used  the sampling quota technique, and  the number of samples in  this study was  70 people.  The research instrument used is with a questionnaire. The data analysis technique uses percentage analysis calculations with the help of the SPSS for windows version 22 and Microsoft Excel programs. The results of this study show that the impact of the use of  PJOK learning technology media  during the face-to-face learning period is limited to the aspect of student responsibility that is in the "moderate" category with a perception rate of 78.6%. It is hoped that  schools must still develop, pay attention to, and maintain the  use of school application media, and a teacher must be able to package the PJOK learning  process so that obstacles in PJOK learning can be minimized properly, and  students must remain enthusiastic  and enthusiastic in physical education learning  with various methods given by the teacher.